Enhanced Phosphorylation of NMDA Receptor 1 Subunits in Spinal Cord Dorsal Horn and Spinothalamic Tract Neurons after Intradermal Injection of Capsaicin in Rats - Zou, Xiaoju (J Neurosci, 2000)
The functional enhancement of NMDA receptors after peripheral tissue injury is proposed to contribute to the sensitization of spinothalamic tract (STT) cells and hyperalgesia. Protein phosphorylation is a major mechanism for the regulation of NMDA receptor function. In this study, Western blots, immunofluorescence double labeling, and the retrograde tracing method were used to examine whether phosphorylation of NMDA receptor 1 (NR1) subunits increases in spinal cord tissue and spinal dorsal horn neurons, especially in STT cells, after injection of capsaicin (CAP) into the glabrous skin of one hindpaw of anesthetized rats. Western blots showed that phosphorylated NR1 protein in spinal cord tissue was increased 30 min after CAP injection. Immunofluorescence double-labeling staining showed no significant difference in the number of the NR1-like immunoreactive neurons in laminae I–VII in the lumbosacral segments (L(4)–S(1)) on the ipsilateral and the contralateral sides 30 min after CAP or vehicle injection. However, the numbers of phospho-NR1-like immunoreactive neurons were significantly increased on the ipsilateral side compared with the vehicle injection group. STT cells were labeled by bilateral microinjections of the retrograde tracer fluorogold into the lateral thalamus, including the ventral-posterior lateral nucleus. Immunofluorescence staining was performed at 30, 60, and 120 min after CAP injection or at 30 min after vehicle injection. There was a significant increase in the proportion of STT cells with phosphorylated NR1 subunits compared either with the contralateral side 30 and 60 min after CAP injection or either side of animals after intradermal injection of vehicle. These results provide direct evidence that NMDA receptors in STT cells are phosphorylated after CAP injection.